Effect of heat treatment on the microstructure and yield strength of a cold-rolled enameling steel. Issue 1 (May 2015) - Peng, D; Yu, Q; Lin, C; An, D; Dai, T; Krakauer, B W; Zhu, M
Abstract: The mechanisms of yield strength reduction of a cold-rolled enameling steel after enamel-fire annealing at 760°C by air cooling, and the effect of the tempering process on the microstructure and yield strength, are studied by combining experiments and thermodynamic calculations. The results show that after heat treatment at 760°C and air cooling, the lump phase, enriched with the element carbon, appears along the ferrite grain boundaries, which leads to yield strength reduction. After tempering at 200°C∼400°C, the lump phase disappears gradually and is transformed to lamellar pearlite as the tempering temperature increases, resulting in the yield strength increasing.